Implementation Path of Intelligent Rehabilitation under the Background of Healthy China Construction - HUANG Guozhi (康复学报)
Improving rehabilitation service capacity is an important part of healthy China construction, and intelligent technology is a powerful mechanism for the development of rehabilitation. This paper reviews the background of national policies for the construction of healthy China, analyzes and summarizes the shortcomings that restrict the improvement of rehabilitation service capacity, and recommendations of the implementation path of intelligent rehabilitation. By elaborating the service process of intelligent rehabilitation, the intelligent technical means suitable for integration are analyzed in detail from the four key links of real-time health detection, remote home intelligent rehabilitation intervention, health classification and evaluation standard system and health intervention standard system in order to build the general framework of the implementation path of intelligent rehabilitation. At the same time, taking hypertension rehabilitation as an example, this paper introduces the intelligent rehabilitation practice exploration and reference mode of hypertension intelligent equipment, hypertension rehabilitation clinical research and hypertension rehabilitation database. Finally, in combination with the concept of intelligent Internet of Everything, the definition of "Rehabilitation Internet of Things" is proposed, and the timing of intelligent rehabilitation in the context of healthy China construction is summarized.